Experimental Investigations on Water Lubricated Hydrodynamic Bearing. (2016) - Tamboli, Ketan; Athre, K.
Abstract: To those unfamiliar with the idea of using water as lubricant may not appear promising since it has low viscosity and corrosive nature on ferrous metals. However, it is used in applications such as bearings of the plants(such as nuclear power plant) in which it is used as the process fluid. In the present work, two hydrodynamic bearings are designed using(i)ESDU charts(ii)Reason and Narang technique(iii)Cameron method(iv)Raimondi and Boyd method. All the parameters are calculated using all above approaches and a comparison of clearance, minimum film thickness and power loss etc. has been made from this a decision on clearance is employed for the manufacture of bearings. The necessary metrological measurements were done with help of dial micrometer guage, optical micrometer and surface roughness tester. The experimentations were carried out with proper maintenance of parameters. The materials used are acrylic (Perspex)for bearings and stainless steel for journals. The results are presented in graphical forms for load carrying capacity, side leakage, power loss etc. for different speeds. It is concluded that(i)the design of water lubricated follows the design procedures laid down for oil lubricated bearings.(ii)Materials to be used needs to be properly surface finished, manufactured with adequate tolerances and to be non-corrosive(iii)The load carrying capacity increases for pressure fed condition and if proper clearance is ensured throughout operation, it could still be enhanced(iv)The power loss and temperature are not major issues.(v)Side leakage can be minimized by properly controlling the feed of the lubricant.